Recent Developments in the Use of Covalent Organic Frameworks for Photocatalytic Water Decontamination - Víctor Cepa-López; Miguel Sánchez-Fuente; Alicia Moya; Rubén Mas-Ballesté (Inorganics)
Water pollution by persistent organic and inorganic contaminants constitutes a significant problem for ecosystems and public health. Organic substances such as dyes, pharmaceutical residues, pesticides, and phenolic compounds are increasingly detected in water due to industrial and agricultural activities. Alongside these, toxic heavy metals contribute to the complexity of water treatment challenges. Conventional remediation methods often fall short due to high operational costs or limited efficiency. In this context, photocatalysis has emerged as a promising approach for pollutant degradation in water under light irradiation. In this sense, covalent organic frameworks (COFs), a class of porous, crystalline materials formed by the covalent linkage of organic units, offer great advantages as photocatalysts. Their tunable electronic properties, structural diversity, and high stability under aqueous conditions make them ideal for visible light-driven processes. This review explores the structural features that govern the photocatalytic activity of COFs, including conjugation, bandgap modulation, and donor–acceptor structures. Mechanistic insights into photocatalytic degradation are also discussed. Finally, examples of pre-designed COFs are presented with their application in the photodegradation of water pollutants, and their main reactive oxygen species (ROS) involved in the photodegradation mechanism. Overall, this review aims to provide a foundation for the rational design of COFs in advanced water treatment technologies.